The Impact of Mandated Corporate Social Responsibility: Evidence from India's Companies Act of 2013 - Dhammika Dharmapala; Vikramaditya Khanna (Center for Economic Studies and ifo Institute (CESifo), 2016)
Firms' Corporate Social Responsibility (CSR) activity has become the subject of a large literature in recent years. This paper analyzes CSR activity using quasi-experimental variation created by Section 135 of India's Companies Act of 2013, which requires (on a “comply-or-explain” basis) that firms satisfying specific size or profit thresholds spend a minimum of 2% of their net profit on CSR. Our analysis uses financial statement and stock price data on Indian firms from the Prowess database, along with hand-collected data from firms' disclosures of CSR activity. By combining a regression discontinuity (RD) framework (based on a nonparametric local polynomial regression approach) with a standard event study, we find a negative and substantial effect on the value of affected firms (relative to unaffected firms) around the crucial event date. This effect seems to be concentrated among firms that are less customer-facing, as indicated by low advertising expenditures. Using a difference-in-difference approach, we find significant increases in CSR activity among firms affected by Section 135, especially in the fraction of firms engaging in CSR spending. The fraction of firms subject to Section 135 that engage in advertising expenditures appears to have declined, consistent with substitution between advertising and CSR. There is no robust evidence of any significant impact on sales or accounting performance, although a modest decline in the return on assets cannot be ruled out. For a subset of large firms, we hand-collect comprehensive CSR data and find that while firms initially spending less than 2% increased their CSR activity, large firms initially spending more than 2% reduced their CSR expenditures after Section 135 came into effect. We explore various explanations for this presumably unintended consequence of Section 135, and also seek to derive some wider implications of this analysis for understanding the role of CSR.
Keywords: K22; 330; corporate social responsibility; India; company law; event study